Automating FPGA-based CSoC platform generation - Siriwardena Wijesundera, Deshya Senelie (2019)
Field Programmable Gate Array (FPGA) based configurable system-on-chip (CSoC) platforms have become a preferred choice for embedded computing systems to meet the increasing demand for shorter Time-to-Market (TTM) and lower Non-Recurring Engineering (NRE) costs, due to both high density and myriad of on-chip hardware and software compute resources. However, the inability of existing tools to effectively exploit these resources to satisfy design constraints, especially from high level specifications such as C/C++, remains a bottleneck for meeting the TTM pressures. In this research, techniques for the automatic generation of a FPGA-based CSoC platform have been proposed to satisfy the area-time design constraints by taking user preferences into account.